ANALISIS PENGGUNAAN KONJUNGSI DALAM TEKS CERPEN KARYA SISWA KELAS XI SMA NEGERI 3 MAKASSAR - Syamriati Syamriati; Usman Usman (Universitas Negeri Makassar, 2022)
Analysis of the Use of Conjunctions in Short Story Texts by Class XI Students of SMA Negeri 3 Makassar. This study aims to describe the function and meaning of the use of conjunctions in short stories by students of class XI SMA Negeri 3 Makassar. The type of research used is qualitative research. Data collection techniques used are reading, note-taking, and discovery techniques. The results showed that first, four functions and three meanings of the use of coordinating conjunctions were found. Second, the use of correlative conjunctions is not found. Third, nine functions and meanings of the use of subordinating conjunctions were found. Fourth, four functions and meanings of the use of conjunctions between sentences were found. Based on the results of this study, it can be said that the function and meaning of the use of conjunctions that are most commonly found are subordinating conjunctions, then coordinating conjunctions, and conjunctions between sentences, while the use of correlative conjunctions is not found in this study.